Comparative performance of culture using swabs transported in Amies medium and the Aptima Combo 2 nucleic acid amplification test in detection of Neisseria gonorrhoeae from genital and extra-genital sites: a retrospective study. Issue 1 (27th October 2011) - Harryman, Lindsey; Scofield, Sara; Macleod, John; Carrington, David; Williams, O Martin; Fernandes, Arnold; Horner, Paddy
Abstract : Background: Nucleic acid amplification tests are being increasingly used for the routine diagnosis of Neisseria gonorrhoeae (GC), although culture remains essential for monitoring antimicrobial resistance. The authors investigated how symptoms and infection site influenced test sensitivity. Methods: This was a retrospective study at two centres of patients diagnosed as having GC by Aptima Combo 2 (AC2) confirmed with Aptima GC and/or culture. Results: The study included 251 men (71%) and 105 women (29%). The sensitivity for AC2 and culture in the lower genital tract of men with symptoms was 99% (95% CI 95% to 100%) and 79% (95% CI 71% to 85%) and for asymptomatic men was 94% (95% CI 69% to 100%) and 29% (95% CI 11% to 56%), respectively. At the rectum, the sensitivity in symptomatic men was 91% (95% CI 57% to 100%) and 55% (95% CI 25% to 82%) and in asymptomatic men 75% (95% CI 47% to 92%) and 44% (95% CI 21% to 69%) for AC2 and culture, respectively. In symptomatic women, the sensitivity from the genital site was 100% (95% CI 95% to 100%) and 53% (95% CI 38% to 68%) and for asymptomatic women 100% (95% CI 87% to 100%) and 47% (95% CI 30% to 65%) for AC2 and culture, respectively. Conclusions: The AC2 with AGC confirmation performs well at genital and extra-genital sites for detecting GC. Culture for GC using transport swabs performs poorly in asymptomatic men, symptomatic and asymptomatic women and at extra-genital sites. With the improved performance of nucleic acid amplification tests and the increase in GC antimicrobial resistance, research is needed into how best to optimise GC culture in settings where direct plating is not feasible.